The Hemingway Short Story : A Study in Craft for Writers and Readers - Lamb, Robert Paul, 1951- (Book collections on Project MUSE., 2013)
This volume analyzes the short story writing of American writer Ernest Hemingway (1899-1961). The author attempts to illuminate Hemingway's's methods of construction and to show how craft criticism complements and enhances cultural literary studies. This study presents close readings of representative Hemingway short stories such as "Soldier's Home," "A Canary for One," "God Rest You Merry, Gentlemen," and "Big Two-Hearted River." The author's examinations of the stories explores not only its biographical contexts -- showing how details, incidents, and characters developed in the writer's mind and notebook as he transmuted life into art -- but also its original, deleted opening and the final text of the story, uncovering otherwise unseen aspects of technique and new terrains of meaning.